A intermediação na saúde: as organizações sociais e suas configurações - Baggenstoss, Salli (Universidade Federal de São Carlos, 2013)
In the organizational universe strategic changes are necessary and generate repercussions. A considerable part of the state hospitals in São Paulo is management by charities that receive the qualification from social organizations and are chosen by government. The main question about this research relates to the (re) adjust at the hospital caused by new strategies of management that comes through health between the State and the Social Organization of Health for hospital management. Understand that the changes occurred in this space: who makes their occupation, it relates, themselves with whom, what are the repercussions, the opposed strength, et cetera. For this way, it has adopted a qualitative approach involving field research and also bibliography research pointed to the subject of the social organizations, its origin and uses in Brazil, the involved questions and the opposed movements to its use. It also was specified the law in São Paulo and the Management Contract, main tool at its disposal that detail kinds and numbers of treatments, values, quality indicators, among others. The used methodology behaved answer inquiries put through the field research together the hospitals and respective manager charities in the State and Municipality, involving also hospital about direct administration for possible comparisons. The resulted data of the research indicated that the qualified charities acted before in health, previous requirement that would give support to attend the specification from de manager contract. Among the findings, it noticed that the creation of the supplemental law got help from agents that make up the social organizations. The choice of the charities is indicated: it is their option to enroll in run the hospital (made by official announcement), and it is the Secretary of Health s option in choosing which applicant (when there are more than one) is the most indicated for the management. Due to a strength oppose consisted specially by people that work for health, advisors and health s union, in search for legitimate occur to events promoted by charities, by unison speech, by publication that point aspects out like numbers and favorable table of contents. Another item noticed is the distribution of the hospitals and the region where the social organizations act, showing the territorial occupation in health by these charities. The managed health differs in hospitals from direct administration by permanent management strategies, a lot of which also available to the hospitals from direct administration offered by own government, which reinforces the role of intermediaries that research suggests.
Keywords: Teoria da organização; Instituições de saúde; Governo; Contrato de gestão; Intermediários; Organizações sociais; Social organizations; Health; Government; Management Contract; Intermediaries; ENGENHARIAS::ENGENHARIA DE PRODUCAO